HUBUNGAN TINGKAT PENDIDIKAN DENGAN PARTISIPASI POLITIK PADA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN DI KECAMATAN SENAPELAN KOTA PEKANBARU TAHUN 2014 - Aang Nofitra; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of the study to analyze and find out how much the level of education related to the political participation of the people in the general election of President and Vice President in 2014. The research problems are How Relationships level of education and political participation in the election of President and Vice President in the District Senapelan Pekanbaru 2014. the type of research used in this research is descriptive with quantitative approach. The data source consists of primary data from respondents beasal primary level a number of 48 respondents, 17 respondents secondary education, higher education amount to 35 respondents and secondary data. The sampling method used Taro Yamane formula and obtained a total sample of 100 respondents . Technical analysis of the data used is the Chi-Square Analysis (x2), crosstab, and hypothesis testing. The results of this study showed that low levels of education dominated the partition of politics , after the chi-square test using SPSS there is no correlation level of education and political participation in District Senapelan Pekanbaru On elections of President and Vice President in 2014 and concluded that the level of education low can affect the height of political participation, vice versa. It is based on the categorization results that generate less educated people , in the category of high political participation relationship , which amounted to 57.1 % . An educated community medium , in the category of most low political participation , which amounted to 17.5 % . A highly educated society , in the category of political participation was as high as 25.4% . Regarding the relationship between the level of education to political participation occurred in Senapelan District entered into there was no correlation with the level of political participation of higher education in the District Senapelan City Pekanabaru the election of President and Vice President in 2014 based on the results of the calculation of the chi -square test using SPSS with value r of 0.330 ( 2 , N = 100 ) = 2.216 ; p > 0.05 ) . It happens that there is no relationship between the level of higher education to political participationkeyword: education, political participation